GAYA PENULISAN ERNEST HEMINGWAY DALAM THE SUN ALSO RISES - Donny Syofyan (Puitika, 2019)
Hemingway is a noted American writer and a mouthpiece of the Lost Generation. His writing style and life attitude of the characters in the novels lent color to the whole world. His words are simple, full of emotion and symbolism and strong emphasis upon dialogue. Any efforts to fathom Hemingway must include his writing style in his novels. The writer’s portrayal of minds are presented through his first masterpiece —The Sun Also Rises.Keyword: style, novel, the Sun Also Rises, America